Analisis Gaji Aparatur Sipil Negara (ASN) Sebagai Objek Harta Bersama Pasca Perceraian - Muhammad Ilham (TAQNIN: Jurnal Syariah dan Hukum, 2021)
The problem of joint property is closely related to the problem of divorce in family relationships, both in divorce and in divorce. The thing to consider after divorce is property, especially in property brought by yourself before getting married and also property after marriage which is also called joint property.This study uses a methodology with a qualitative approach. As well as the method used in the research based on the approach used, the normative juridical method is used.In his analysis it was found that if the divorce by the State Civil Apparatus resulted in a difference in the distribution of joint property, this was seen from which party wanted a divorce. If it is from the husband's side and the husband is also an ASN, then joint property is given. But if it's from the wife who wants it, then she doesn't get that part.